Ophiocordyceps xuefengensis sp. nov. from larvae of Phassus nodus (Hepialidae) in Hunan Province, southern China - Wen, Ting-Chi; Zhu, Ru-Cai; Kang, Ji-Chuan; Huang, Ming-He; Tan, Dian-Bo; Ariyawansha, Hiran; Hyde, Kevin D.; Liu, Hao (Phytotaxa, 2013)
An entomogenous taxon, associated with larvae of Phassus nodus (Hepialidae) collected from Xuefeng Mountains, Hunan Province, China, was found to be a new species, Ophiocordyceps xuefengensis sp. nov. It differs from similar species in having long stromata, without a sterile apex, narrow asci, long ascospores and by its occurrence on Phassus nodus in living root or trunk of Clerodendrum cyrtophyllum. Combined sequence data from the 5.8S-ITS rDNA, nrSSU, EF-1α, and RPB1 gene loci also confirmed the distinctiveness of this new species. It is presently the world’s largest known Cordyceps sensu lato species.